Complex acoustic gravity wave behaviors to some mathematical models arising in fluid dynamics and nonlinear dispersive media - Bulut, Hasan; Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet; Akturk, Tolga (Springer, 2018)
This study acquires the wave solutions of the two well-known nonlinear models, namely; the modified Benjamin-Bona-Mahony and the coupled Klein-Gordon equations. The modified Benjamin-Bona-Mahony is a nonlinear model that describes the long surface gravity waves of small amplitude and the coupled Klein-Gordon equation describes the quantized version of the relativistic energy-momentum relation. We successfully acquire some new solutions to these models such as kink-type and soliton solutions in complex hyperbolic functions form. We plot the 3D and 2D surface of the all the obtained solutions in this study. The mathematical approach used in this study is the sine-Gordon expansion method.
Keywords: The SGEM; The mBBM equation; The coupled KG equations; Soliton; Kink-type